Drug use of children in the community assessed through pharmacy dispensing data - Schirm, Eric (Blackwell Science Inc, 2000)
AIMS: To determine the extent of drug use in children and the types of drugs that children use. METHODS: Cross-sectional study and cohort study, using computerized pharmacy dispensing records for all children aged 0–16 years in the northern part of The Netherlands in 1998. The main outcome measures were proportion of children that used drugs (per sex and age group), mean number of drugs per child, 10 most widely used drug groups and cumulative proportions of drugs users (per drug group) during the first 2 years of life. RESULTS: Drug use was the highest among infants, decreased till adolescence and increased from there. Overall, approximately 60% of all children used at least one drug in 1998. At younger ages, boys used more drugs than girls and at older ages girls used more drugs than boys. Systemic antibiotics were used by 21% of the children and were by far the most widely used drugs. Other frequently used drugs were analgesics (10%), corticosteroids for dermatologic use (9%), anthistamines (8%) and antiasthmatics (7%). Approximately 10% of the children had used at least one drug at the age of 1 month and at the age of 2 years this proportion was 81%. CONCLUSIONS: The majority of children was exposed to one or more drugs and this exposure started at very young age. This shows the importance of good guidelines for drug use in children and emphasizes the necessity of research of pharmacokinetic and pharmacodynamic properties in children to obtain safety, efficacy and quality evidence of these drugs.